IN VITRO EXPLORATION OF BIOCOMPATIBILITY AND SURFACE PROPERTIES OF TWO DIFFERENT MATERIALS: HYBRID CERAMIC AND HYBRID RESIN - Roxana Nicoleta Ionescu; Dana-Cristina Bodnar; Bianca Voicu Balasea; Florentina Gherghiceanu; Alexandra Ripszky Totan; Silviu Mirel Pituru; Cristian Funieru; Marina Melescanu-Imre (Romanian Journal of Oral Rehabilitation)
Objectives: This study evaluates two dental materials—modified resin with glass fiber (Trinia) and hybrid ceramic (Vita Enamic)—for implant crown restoration, focusing on biocompatibility. Material and Methods: Using a CAD/CAM system, two Vita Enamic blocks and a multidirectional network disc of Trinia were fabricated. A human gingival fibroblasts line (HFIB-G) was used to investigate cell viability and cytotoxicity of the dental materials through MTT, respectively LDH assays.